TEKNIK PENDUKUNG KEPUTUSAN DALAM MENENTUKAN PENERIMA KARTU INDONESIA PINTAR KULIAH (KIP-KULIAH) DENGAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Setiyo Prihatmoko; Sumaryanto Sumaryanto; Fujiama Diapoldo Silalahi (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2021)
In realizing accessibility and equalizing of high-quality education and relevant to community interests for progress, independence, and prosperity. The government is obliged to increase access and learning opportunities at universities and to prepare intelligent and competitive Indonesian people. There is no term “poor children are being banned fromschool or college” in this country. Those who are less able and have achievements, must continue to advance to higher education through the Indonesian Smart College Card or KIP- College from the Government. This research is to create a decision support technique in determining KIP-College recipients using the Analytical Hierarchy Process (AHP) method so that it is right on target. Besides that, it is also to assist operators in determining KIP-College recipients, especially in processing and selecting data for parents who are truly from underprivileged economic classes.